Corruption in Latin America: Stereotypes of politicians and their implications for affect and perceived justice - Ramos, M; Moriconi, M (SAGE Publications, 2017)
Latin America has experienced a series of recent corruption scandals, resulting in an unprecedented uncertainty in political leadership across the whole region. Within this context, we have conducted a survey study comprising 9 countries in Latin America (n=1,250) examining the stereotype content of politicians. We tested a dual effects model in which the stereotypes of politicians were predicted to shape perceptions of justice directly and indirectly through the activation of affect. Our findings revealed that politicians tended to be stereotyped with negative morality traits and with a certain degree of negativity across other stereotype dimensions. Results supported a positive direct effect of morality on perceived justice and a positive indirect effect through the activation of affect. We discuss the implications of these findings for the current political context in Latin America and also for our understanding of perceptions about politicians and their relationship with leader and power legitimacy.